A new method for calculating the theoretical dry flue gas volume of metallurgical gas. (December 2020) - Ye, Yalan; Jiang, Wenhao; Wang, Hongming; An, Xiang
Abstract: Aimed at the limited engineering condition that only gas calorific value but not gas composition can be provided, a new theoretical combustion calculation method based on gas calorific value was proposed, which is suitable for calculating the theoretical dry flue gas volume of metallurgical gas. In the new method, three simplified models were proposed, including blast furnace gas (BFG) model, Linz–Donawitz converter gas (LDG) model and coke oven gas (COG) model. The simplified models were respectively derived from the original model of theoretical combustion calculation, according to the composition characteristics of each metallurgical gas. Finally, the proposed models were verified through large sample of BFG, LDG and COG. The verification results show that the new models for calculating the theoretical dry flue gas volume of metallurgical gas all have high accuracy. The average relative errors of BFG model, LDG model and COG model are only 0.35%, 0.12%, 0.64% respectively. Thus, the new method proposed in this paper is reasonable and feasible. It can meet the accuracy requirement of engineering and can provide a new way for theoretical combustion calculation of metallurgical gas.